2021
DOI: 10.1111/php.13445
|View full text |Cite
|
Sign up to set email alerts
|

Water Effect on Peroxyoxalate Kinetics and Mechanism for Oxalic Esters with Distinct Reactivities

Abstract: The peroxyoxalate reaction is being widely used for various analytical and bioanalytical applications, and however, few mechanistic studies are performed in aqueous media, important mainly for bioanalytical applications, where low chemiluminescence emission quantum yields are obtained. In this sense, we report here kinetic studies on the peroxyoxalate reaction, using two commercially available and widely utilized esters, bis(2,4‐dinitrophenyl) oxalate (DNPO) and bis(2,4,6‐trichlorophenyl) oxalate (TCPO), in 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Additionally, it was observed that with both esters Φ S values increased up to [H 2 O] = 0.7 mol L −1 , reaching chemiexcitation yields as high as 5 × 10 −3 E mol −1 (Table 1), decreasing afterwards for superior water concentrations (70); constituting the first report of a systematic increase in Φ S with water concentration for the PO‐CL reaction. It was hypothesized that the chemiexcitation efficiency may be related to a solvation effect involved with the bimolecular interaction between the HEI and ACT, within the CIEEL sequence (70). This may occur due to a medium polarity effect, or even due to a specific molecular water effect that could stabilize the generated radical‐ion pair through hydrogen‐bonding (Scheme 5) (70).…”
Section: Mechanistic Studies On the Peroxyoxalate System In Aqueous M...mentioning
confidence: 76%
See 4 more Smart Citations
“…Additionally, it was observed that with both esters Φ S values increased up to [H 2 O] = 0.7 mol L −1 , reaching chemiexcitation yields as high as 5 × 10 −3 E mol −1 (Table 1), decreasing afterwards for superior water concentrations (70); constituting the first report of a systematic increase in Φ S with water concentration for the PO‐CL reaction. It was hypothesized that the chemiexcitation efficiency may be related to a solvation effect involved with the bimolecular interaction between the HEI and ACT, within the CIEEL sequence (70). This may occur due to a medium polarity effect, or even due to a specific molecular water effect that could stabilize the generated radical‐ion pair through hydrogen‐bonding (Scheme 5) (70).…”
Section: Mechanistic Studies On the Peroxyoxalate System In Aqueous M...mentioning
confidence: 76%
“…For both TCPO and DNPO in DME/water mixtures, the recorded perhydrolysis rate constants are several orders of magnitude higher than the corresponding hydrolysis rate constants (Scheme 5) (70). Additionally, it was observed that with both esters Φ S values increased up to [H 2 O] = 0.7 mol L −1 , reaching chemiexcitation yields as high as 5 × 10 −3 E mol −1 (Table 1), decreasing afterwards for superior water concentrations (70); constituting the first report of a systematic increase in Φ S with water concentration for the PO‐CL reaction. It was hypothesized that the chemiexcitation efficiency may be related to a solvation effect involved with the bimolecular interaction between the HEI and ACT, within the CIEEL sequence (70).…”
Section: Mechanistic Studies On the Peroxyoxalate System In Aqueous M...mentioning
confidence: 85%
See 3 more Smart Citations